Limited dorsal myeloschisis in three cats: a distinctive form of neural tube defect. Issue 1 (June 2020) - Butterfield, Sarah; Garcia-Gonzalez, Beatriz; Driver, Colin J; Rusbridge, Clare
Case series summary: The aim of this case series was to describe the clinical presentation, imaging findings and histopathology of three cats with limited dorsal myeloschisis (LDM). The history, examination and MRI sequences were reviewed in three cases presented to a single referral hospital. The surgery report and histopathology were described in two cases. All cats were young (10 weeks old, 5 months old, 4 years old), presenting with varying degrees of progressive paraparesis. All had a midline skin defect overlying the spinal column that was either sunken or saccular, containing fluid thought to be cerebrospinal fluid. MRI sequences demonstrated tissue extending from the dura through an overlying bifid spinous process and attached to the dermis, with associated spinal cord tethering, atrophy and syringomyelia. Lesions were located at L2–L3, T8–T9 and L4. Histopathology described a fibroneural stalk with a glio-ependymal lining, surrounded by glial nests and nerve fibres. The youngest and most severely affected was euthanased, while the other two underwent surgery. Both regained independent ambulation with persistent paraparesis; however, one required ongoing management of urinary incontinence. Relevance and novel information: LDM is a primary neural tube defect that may result in neurological deficits, including bladder dysfunction, and is characterised by a fibroneural stalk between the dermis and the spinal cord. Distinct MRI features, such as a visible intrathecal tract, dorsally tethered cord and syringomyelia, help distinguish this condition from the clinically similar dermoid sinus. The presence of progressive neurological signs, with a palpable midline defect overlying the affected spinal cord segment, may raise suspicion for this clinical entity in veterinary patients.